Equilibrium in a Production Economy with an Income Tax - II, Wilbur John Coleman (Econometrica, 1991)
A state-dependent income tax is incorporated into an intertemporal production economy. Methods are developed for establishing the existence and uniqueness of an equilibrium, and for explicitly constructing this equilibrium. Some tax-policy experiments are suggested, the results of which may have important implications in quantifying the effects of various tax policies.